Trabajo social y discapacidad: intervención desde el departamento de calificación del Ministerio de Salud Pública - Alava Barreiro, Leila Maria (2020)
People with disabilities are considered to be those who have long-term physical, mental, intellectual, and sensory deficiencies that, by interacting with various contexts, may impede their full and effective participation in society, therefore, the objective of this research was to analyze the intervention of the Social Worker for the granting of the disability card in the qualification department of the Ministry of Public Health of Ecuador. The methodology used was of a non-experimental type, supported by the descriptive, bibliographic method; The scientific logical method was applied: inductive-deductive with a qualitative approach, a methodology that enabled the stated objective to be met. As a result, emphasis is placed on the intervention of the professional in Social Work, which consists of carrying out the social assessment of the user, in which socioeconomic, individual and family factors are addressed, for which the baremo matrix is ​​used, which allows granting a qualification that added to the one of the final diagnosis of the doctor determines a qualification to grant or not the disability card. The intervention of the professional in Social Work is essential, as it is an agent of change and social inclusion, which executes activities and processes in search of improvements in users with disabilities, reducing barriers that directly limit their participation in society.